Nos caminhos da dupla consciência: socialismo indo-americano, libertação e descolonização na América Latina - Gonçalves, Bruno Simões (2014)
The present work is a study of the historical and philosophical background of Latin American double consciousness. Since the beginning of America, Latin American identity has been forged through a breakup and a tension between the logic of coloniality of power (one as a principle) and the logic of critical mestizaje (two as a totality). In the first one, difference is radically denied; in the second one, it is legitimized as a foundation of reality. This originates a dialectic of extremes proper to Latin America s formation, in which different memories and times are mixed in a heterogeneous and contradictory totality. In the beginning of the XX century, the work of the thinker José Carlos Mariátegui was the expression of such tension. Being the first great Marxist thinker of Peru, Mariátegui defended the idea that there is an agonizing struggle between two souls in Latin American consciousness: on the one hand, the positivist decaying edifice built from capitalism; on the other hand, the new impetus, the passionate desire in search of Indo-American socialism, capable of bringing together indigenous world, revolution, spirituality and poetic imagination in the same movement of the subversion of Latin America s historical double consciousness. The tradition of a critical thinking that can express the way of life of different populations of Latin America continued throughout the XX century, when the idea of a critical mestizaje develops in the literature, the philosophy and the social thinking of the whole continent. It is in this context that the category of liberation is constituted as an expression proper of the Latin American critical thinking and, in the beginning of the XXI century, unfolds in the search for an intercultural and decolonized praxis. Considering this long-lasting historical arc, the thesis brings subsidies to a reading of the current context of capitalism s structural crisis, from the standpoint of the intersubjective dimension as divided historical consciousness. And it puts forward approaches to the construction of a new historical sense for the contemporary social struggles